EVALUASI KINERJA DAN PERBAIKAN STRUKTUR BETON GEDUNG PENDINGIN AIR = EVALUATION ON THE PERFORMANCE OF AND REPAIR OF THE CONCRETE STRUCTURE OF A COOLING WATER TOWER - Hendro Ahmad Fauzi (Jurnal Material Komponen dan Konstruksi, 2013)
This paper presents the evaluation of performance and strenght ofstructure by visual inspection and quality testing of concrete in the field by using aSchmidt hammer and UPV. The evaluation on the performance of the structure,strength columns, beams and plates refer to SNI-2847-2002, in which theimplementation of earthquake loads was based on SNI-1726-2002.The paperproposes improvements and retrofitting necessary structures. SAP2000 is usedfor structural analysis necessary to obtain the required strength values (Ru).Beton2000 is used for structural analysis of existing conditions in order to get thedesigned strength values (Rn). The structure components are in safe condition ifits design strength is greater or equal than required strength or (Ø.Rn) ≥ Ru.Improvements were made to the structural element by coating and injectionmethods.Keywords : structural performance evaluation, improvement AbstrakMakalah ini menyajikan evaluasi kinerja dan kekuatan struktur denganmetode pemeriksaan secara visual dan pengujian mutu beton di lapangandengan alat Schmidt hammer dan UPV. Evaluasi kinerja struktur, kekuatankolom, balok serta pelat mengacu pada SNI-2847-2002, dengan penerapanbeban gempa berdasarkan SNI-1726-2002, serta memberikan usulan perbaikandan perkuatan struktur yang diperlukan. SAP 2000 digunakan untuk analisisstruktur guna mendapatkan nilai kuat perlu (Ru). Beton 2000 digunakan untukanalisis struktur kondisi existing guna mendapatkan kuat rencana (Rn).Komponen struktur dikatakan aman jika kuat rencana lebih besar atau samadengan kuat rencana atau (ф . Rn) ≥ Ru. Perbaikan elemen struktur dilakukandengan metode coating dan injeksi..Kata kunci : evaluasi kinerja struktur, metode perbaikan